Application of Antimicrobial peptides in Plant-Disease Control - Thitiporn Ditsawanon; Sittiruk Roytrakul; Nonglak Parinthawong (My University, 2024)
Plant pathogens are a significant and urgent issue mainly in agricultural countries. Disease control using chemicals and antibiotics can cause widespread negative impacts, particularly on fresh vegetables and agricultural raw materials. These could affect national food insecurity. Antimicrobial peptides (AMPs) are one of the effective solutions because of theirs remarkable antimicrobial action mostly on bacteria and fungi, the primary causes of plant-infected diseases. AMPs are present in common living things, both in prokaryotes and eukaryotes, these are the natural defenses in organisms. Each type of AMPs exhibits distinct microbial targets through various mechanisms. Some AMPs kill microbes in a few seconds after contact with target cells, some AMPs stimulate the antibiotic effects, while some AMPs exhibit superior results than antibiotics. AMPs work by two different mechanisms: the direct bactericidal mechanism that involves interaction with the bacterial membrane and results in cell lysis, and the indirect bactericidal mechanism that involves penetration without causing cell lysis but inhibiting the synthesis of DNA, RNA, and proteins. Current AMPs research reveals promising outcomes at the laboratory level. Further studies will focus on the actual environment and the outbreak area respectively.
Keywords: Antimicrobial Peptides and Activities